Description of PICU Unplanned Readmission*. Issue 6 (June 2016) - Kotsakis, Afrothite; Stevens, Derek; Frndova, Helena; Neal, Richard; Williamson, Grace; Mohseni-Bod, Hadi; Parshuram, Christopher S.
Abstract : Objectives: ICU readmission within 48 hours of discharge is associated with increased mortality. The objectives of this study were to describe the frequency of, factors associated with, and outcomes associated with unplanned PICU readmission. Design: A retrospective case-control study was performed. We evaluated 13 candidate risk factors and report patient outcomes following readmission. Subgroup analyses were performed for patients discharged from the cardiac PICU and medical-surgical PICU. Setting: The study was undertaken at the Hospital for Sick Children, Department of Critical Care Medicine. Patients: Eligible patients were discharged from the PICU to an inpatient ward between December 2006 and January 2013. Case patients were readmitted to the PICU within 48 hours of discharge. Measurements and Main Results: There were 10, 422 eligible patient discharges; 264 (2.5%) were readmitted within 48 hours. In the univariable analysis, unplanned readmission was associated with PICU patient admissions of younger age, lower weight, greater duration of PICU stay, greater cumulative stay in PICU in the past 2 years, higher Pediatric Logistic Organ Dysfunction score on PICU discharge, discharge outside goal discharge time (06:00–11:59 hr), use of extracorporeal organ support during ICU stay, greater Bedside Pediatric Early Warning Score, at discharge and discharge from the cardiac PICU. In the multivariable analysis, the factors most significantly associated with unplanned PICU readmission were length of stay more than 48 hours, greater cumulative length of PICU stay in the past 2 years, discharge from cardiac PICU, and higher Pediatric Logistic Organ Dysfunction and Bedside Pediatric Early Warning Scores on index discharge. Mortality was 1.8 times ( p = 0.03) higher in patients with an unplanned PICU readmission compared with patients during their index PICU admission. Conclusions: The only potentially modifiable factors we found associated with PICU readmission within 48 hours of discharge were discharge time of day and the Pediatric Logistic Organ Dysfunction and Bedside Pediatric Early Warning Scores at the time of PICU discharge.